Translation of Lithuanian Literature into Italian: An Overview of the Decade (2008–2018) - Cerri, Adriano (Vertimo studijos, 2018)
[full article and abstract in Lithuanian; abstract in English]The article presents an overview of translations from Lithuanian into Italian during the last decade (2008–2018). All translations of Lithuanian works into Italian that are known to the author are reviewed by genre: prose, poetry, essay and theatre. The analysis reveals that poetry is the most translated genre, but several significant novels and essays were also published during the period under review. In the analysis, the terminus post quem is 2007, when Lithuania was an honorary guest of the Turin Book Fair. The aim of this review is not only to update data on Lithuanian literature in Italy, but also to discuss its current situation. The statistics show a positive trend, i.e. there is a steady increase in the number of translated works: over the last five years, the number of translations has almost doubled compared to 2005–2008. However, the constant increase in the number of translations rather than in the number of translators shows that such results were not achieved through external events, but by the work of several dedicated, tireless translators.
Keywords: Lithuanian literature; translations of Lithuanian literature into Italian; Turin Book Fair